Estudo de gerenciamento SNMP em PABX híbridos - Paula, André Domingues de (2015)
This work aims to conduct study of SNMP management protocol applied in hybrid private telephone exchanges that have analog capabilities, digital, IP and features that these devices offer, in order to implement the protocol in a real system, get reports that management allows and analyze the information obtained.